2014
DOI: 10.1007/s11746-014-2545-8
|View full text |Cite
|
Sign up to set email alerts
|

Influence of a Diet Enriched with Perilla Seed Bran on the Composition of Omega‐3 Fatty Acid in Nile Tilapia

Abstract: GIFT during feeding time, contributing to an increase in its nutritional value.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…h/H ratio provides effects of fatty acids being apprehensible on cholesterol metabolism. Thus, it is preferred that the ratio shows higher value (Santos et al, 2014;Pleadin et al, 2017). h/H was lower in wild and cultured brown trout than in Atlantic salmon (Table 3).…”
Section: Lipid Quality Indicesmentioning
confidence: 99%
“…h/H ratio provides effects of fatty acids being apprehensible on cholesterol metabolism. Thus, it is preferred that the ratio shows higher value (Santos et al, 2014;Pleadin et al, 2017). h/H was lower in wild and cultured brown trout than in Atlantic salmon (Table 3).…”
Section: Lipid Quality Indicesmentioning
confidence: 99%
“…Oliveira et al (2018) reported that the lowest AI and TI values are very important to judge the nutritional quality of fatty acids when low risk of cardiovascular disease is in question. We found that the AI values of fish flesh fatty acid profiles were higher than those reported from freshwater fish species, such as Oreochromis niloticus (0.56) (Oliveira et al, 2018), Nile tilapias (0.67) (dos Santos et al, 2014), Tilapia roja (1.42), barbado (1.18) and jau (1.00) (dos Santos et al, 2014).…”
Section: Discussionmentioning
confidence: 66%
“…(1.18) and jau (1.00) (dos Santos et al, 2014). Abbreviations: AI, Atherogenic index; FA, Fatty acid; GSO, Grape seed oil; HH, Hypocholesterolaemic/Hypercholesterolaemic fatty acid ratio; TI, Thrombogenic index.…”
Section: Discussionmentioning
confidence: 99%
“…An early study using Entrox-coated PSO capsules, designed to resist fatty acid release in the stomach's acidic environment and enhance absorption in the intestine, found no significant difference in short-term α-linolenic acid pharmacokinetics compared to uncoated capsules [ 73 ]. However, a later study by Dos Santos et al [ 74 ], designed to explore the impact of the perilla seed bran diet on ω-3 fatty acid composition in tilapia fillets, observed that the perilla seed bran diet significantly influences tilapia fillet lipid composition, with a remarkable 384 % increase in α-linolenic acid incorporation and a 74.15 % reduction in total saturated fatty acids, resulting in an improved ω-6/ω-3 fatty acid ratio.…”
Section: Recent Research Progressesmentioning
confidence: 99%